2011
DOI: 10.1158/1940-6207.capr-10-0006
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Drug Delivery Systems of Curcumin for Cancer Chemoprevention

Abstract: From ancient times, chemopreventive agents have been used to treat/prevent several diseases, including cancer. They are found to elicit a spectrum of potent responses including anti-inflammatory, anti-oxidant, anti-proliferative, anti-carcinogenic, and anti-angiogenic activity in various cell culture and some animal studies. Research over the past four decades has shown that chemopreventives affect a number of proteins involved in various molecular pathways that regulate inflammatory and carcinogenic responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
249
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(258 citation statements)
references
References 92 publications
1
249
0
8
Order By: Relevance
“…PHAs are also useful as stereoregular compounds which can serve as chiral precursors for the chemical synthesis of optically active compounds (32,254). Such compounds are particularly used to synthesize the micro-and nanosphere of PHAs as biodegradable carriers or drug delivery systems for controlled release of therapeutics such as medicines, hormones, insecticides and herbicides into systemic circulation are receiving attention (30,31,253,255,256). According to Sudesh et al, PHAs have the oil absorption and retention capacities which offer commercial application value in the cosmetics and skin care industries (257).…”
Section: (2) Medical and Pharmaceutical Applicationsmentioning
confidence: 99%
“…PHAs are also useful as stereoregular compounds which can serve as chiral precursors for the chemical synthesis of optically active compounds (32,254). Such compounds are particularly used to synthesize the micro-and nanosphere of PHAs as biodegradable carriers or drug delivery systems for controlled release of therapeutics such as medicines, hormones, insecticides and herbicides into systemic circulation are receiving attention (30,31,253,255,256). According to Sudesh et al, PHAs have the oil absorption and retention capacities which offer commercial application value in the cosmetics and skin care industries (257).…”
Section: (2) Medical and Pharmaceutical Applicationsmentioning
confidence: 99%
“…[11][12][13] Because of its hydrophobic nature and poor bioavailability, the clinical development of curcumin as a "medicine" is dependent upon developing a nanocarrier for efficient transport in the body. 12,14,15 Recently, several curcumin nanoformulations, such as polymer nanoparticles, selfassemblies, nanocrystal dispersions, nanoemulsions, lipid nanoparticles, and protein-based drug delivery systems, have shown improved solubility, stability, and bioavailability of the curcumin molecule. [14][15][16][17][18][19][20] Moreover, curcumin nanoformulations have demonstrated improved cellular uptake in cancer models that increases the chance of a positive therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…After intraperitoneal administration of 0.1 g/kg, the plasma level peaked (2.25 mg/mL) at 15 minutes and declined rapidly within 1 hour (36). To avoid the low bioavailability of curcumin for the clinical application, various advanced drug delivery systems, such as nanoparticles, liposomes, nanoemulsions, and the combination of the adjuvants have been designed, but their biopharmaceutical attributes need to be further validated (35,37). In our E.G7/OT-1 animal model, we found that the critical time for T-cell activation is the first 3 days after adoptive therapy.…”
Section: Discussionmentioning
confidence: 97%